A Comprehensive Review of Smart Blind Stick: Enhancing Independence and Safety for the Visually Impaired - Nikunjkumar Nayak (International Journal of Intelligent Systems and Applications in Engineering, 2024)
Vision is a beautiful gift of God. With the vision, we can see this beautiful world. The significant challenge faced by individuals with visual impairments is accurately discerning their location in unfamiliar environments. With the recent surge in the population of the visually impaired, there has been a demand to focus on developing blind sticks for their ease of life. Blind sticks are equipped with a multitude of features aimed at improving the movement and security of individuals with visual impairments. Sensor technology forms the foundation of these devices, incorporating sensors like ultrasonic, infrared, or LiDAR to identify obstacles and offer immediate feedback to the user. Haptic feedback mechanisms employ vibrations or tactile signals to alert users of nearby obstacles or changes in terrain, further enhancing their awareness of the surroundings. The foldable design of blind sticks allows for convenient storage and portability when not in use, while their lightweight construction ensures ease of handling and minimizes strain on the user. The adjustable length feature enables customization to accommodate the height and preferences of each user. Constructed from durable materials, these sticks are designed to withstand regular use in various environments, ensuring longevity and reliability. With an ergonomic handle for comfortable grip during extended use, blind sticks also offer integrated audio feedback, providing auditory cues or voice prompts to aid in navigation and obstacle detection. Some models even offer connectivity options such as Bluetooth or GPS capabilities, expanding their functionality. Thanks to its enduring battery life, users can depend on their blind sticks for prolonged durations without the necessity for frequent recharging. These combined features make blind sticks essential aids for people with visual impairments, encouraging them to move through their surroundings with greater confidence and autonomy.